2010
DOI: 10.1007/s00134-009-1745-4
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava collapsibility to guide fluid removal in slow continuous ultrafiltration: a pilot study

Abstract: IVC ultrasound is a rapid, simple, and non-invasive means for bedside monitoring of intravascular volume during SCUF and may guide fluid removal velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 18 publications
2
56
0
1
Order By: Relevance
“…It remains to be established whether a different approach, IVCCI serial determination -based, would have prevented or reduced the occurrence of ARD diuretic-related by more careful tailoring of diuretic therapy within the first 48 hours. On the basis of our results, it is also reasonable to speculate that renal impairment in CHF patients may be frequently related to subclinical condition of subtle intravascular volume depletion, whose relatively high (>40%) IVC collapsibility is a reliable marker (31). Actually in our study (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It remains to be established whether a different approach, IVCCI serial determination -based, would have prevented or reduced the occurrence of ARD diuretic-related by more careful tailoring of diuretic therapy within the first 48 hours. On the basis of our results, it is also reasonable to speculate that renal impairment in CHF patients may be frequently related to subclinical condition of subtle intravascular volume depletion, whose relatively high (>40%) IVC collapsibility is a reliable marker (31). Actually in our study (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Meanwhile, glomerular filtration is simultaneously damaged by a peculiar type of unfavorable vasomotor kidney reaction (14,15) consisting in intense vasoconstriction of the afferent arteriolar bed, as elicited by macula densa chemoceptor apparatus highly sensitive to increased delivery of sodium to tubules due to diuretic administration. According to several authors (31,38) this "vasomotor nephropathy" could be minimized using slow mechanical fluid removal by ultrafiltration. In this manner, we could avoid engaging renal excretory pathways and their inherent tubulo-glomerular feedback, whose role in nephrotoxic effect of diuretics in syndromes with reduced effective circulating volume (CHF, cirrhosis of the liver) has been focused in other studies (38,39).…”
Section: Diuretic-related Wrf: Interpretative Theoriesmentioning
confidence: 99%
“…Barbier et al and M Feissel et al demonstrated clearly that respiratory variation of the IVC reliably predicts fluid responsiveness [20,21]. Conversely, in acutely decompensated heart failure patients, the rate of fluid withdrawal during haemodialysis can be guided by intermittent evaluation of the respiratory induced alterations of the IVC diameters [22]. In this particular study, hypotension was observed in those patients with an IVC variation of > 30%.…”
Section: Mechanical Ventilator Induced Intra-thoracic Pressure Changementioning
confidence: 62%
“…Also, the IVC-CI has been used to follow acute volume changes. Patients undergoing ultrafiltration with a total ultrafiltrate production of 5,780 mL, had a significantly increased IVC-CI (p \ 0.001), while there was no change in mean arterial pressures, heart rate, or the IVC diameter [35].…”
Section: Ultrasonographymentioning
confidence: 99%